2015
DOI: 10.3390/jfb6030667
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and in Vitro Evaluation of Nonwoven Type I Collagen/Poly-dl-lactic Acid Scaffolds for Bone Regeneration

Abstract: Poly-dl-lactic acid (PDLLA) was blended with type I collagen to attempt to overcome the instantaneous gelation of electrospun collagen scaffolds in biological environments. Scaffolds based on blends of type I collagen and PDLLA were investigated for material stability in cell culture conditions (37 °C; 5% CO2) in which post-electrospinning glutaraldehyde crosslinking was also applied. The resulting wet-stable webs were cultured with bone marrow stromal cells (HBMSC) for five weeks. Scanning electron microscopy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 60 publications
3
23
0
Order By: Relevance
“…Therefore, PDLLA has been used in drug delivery systems or in the rare TE applications requiring low strength scaffolds [43]. As a consequence, PDLLA nanofibers were rarely electrospun for TE purposes, unless the polymer is blended with other biodegradable polymers [53][54][55].…”
Section: Poly(lactic Acid) (Pla)mentioning
confidence: 99%
“…Therefore, PDLLA has been used in drug delivery systems or in the rare TE applications requiring low strength scaffolds [43]. As a consequence, PDLLA nanofibers were rarely electrospun for TE purposes, unless the polymer is blended with other biodegradable polymers [53][54][55].…”
Section: Poly(lactic Acid) (Pla)mentioning
confidence: 99%
“…Due to their good biocompatibility, the PLA-based materials were extensively used in the field of tissue engineering. However, in order to obtain better optimized scaffolds and to increase cell proliferation and cell adhesion on their surface, PLA have been mixed with other polymers, such as collagen, gelatin or graphene oxide [44,45]. For instance, Qiao et al [45] found that PLA/collagen electrospun fibrous scaffolds at a 60:40 weight ratio showed greatest stability, cell attachment, cell proliferation, and osteogenic differentiation of bone marrow stromal cells after five-week culture period.…”
Section: Discussionmentioning
confidence: 99%
“…It has facilitated numerous humans due to the long-term dedication to the structure, function, and growth mechanism of biological tissues against the background of cellular biology and bioengineering development. Scaffolds, as the carriers of cell adhesion and growth, play a decisive role in tissue engineering and have been used in many branches, such as bone regeneration [69], blood vessel [70], and neural system [71]. Ideal scaffolds should not only have suitable construction beneficial to cells growing but also have excellent biofunctionality because the behavior of cells can be easily influenced by the local environment, including some biochemical and mechanical cues [72].…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Many other biomaterials such as collagen and graphene oxide are gradually introduced to polymerize with PLA or PLGA in order to obtain optimized scaffold structures. Qiao et al [69] blended type I collagen with PDLLA and finally found that when type I collagen occupied a proportion of 40% in the scaffolds, PDLLA/collagen scaffolds showed greatest stability, cell proliferation, and osteogenic differentiation after five-week cultivation. As is shown in Figures 3(a) Shin et al [72] successfully fabricated hybrid fiber matrices GO-PLGA-Col composed of PLGA and collagen (Col) impregnated with GO via an electrospinning technique.…”
Section: Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation